An amphiphilic manganese porphyrin-paired ionic copolymer: a highly efficient biphasic transfer catalyst for the selective oxidation of olefins with O2 and TBHP. (10th July 2019) - Mokary Yazdely, Tahereh; Ghorbanloo, Massomeh; Hosseini-Monfared, Hassan
Abstract : A novel amphiphilic manganese porphyrin-paired ionic copolymer, {ADA-INA-[Mn(TPPS)(OAc)]} n, was prepared by the self-assembly process of non-cross-linked amphiphilic polymeric ligands with inorganic species. Abstract : A novel amphiphilic manganese porphyrin-paired ionic copolymer, {ADA-INA-[Mn(TPPS)(OAc)]} n, was prepared by the self-assembly process of non-cross-linked amphiphilic polymeric ligands with inorganic species. Thus, {ADA-INA-[Mn(TPPS)(OAc)]} n was prepared from Mn(TPPS)(OAc) and poly{[3-(acryloylamino)propyl]dodecyldimethylammonium nitrate}- co -{( N -isopropylacrylamide)12 }. The physicochemical properties of the synthesized catalyst were characterized by FT-IR, SEM and UV-vis spectroscopy. The compound {ADA-INA-[Mn(TPPS)(OAc)]} n showed the capability of catalyzing the oxidation of olefins in solid–liquid biphasic reaction systems with high catalytic activity and selectivity. The oxidation of styrene, α-methylstyrene, cis -cyclooctene, 1-octene and 1-decene, catalyzed by the reaction-controlled phase transfer catalyst {ADA-INA-[Mn(TPPS)(OAc)]} n using O2 and TBHP in a biphasic medium was investigated. After the catalytic reaction, in the solid–liquid biphasic system, the catalyst could be conveniently recovered and steadily reused without a change in the catalyst structure. The unique amphiphilic catalyst structure was revealed to be responsible for the catalyst's excellent performance in the oxidation of olefins with O2 and TBHP by accelerating the mass transfer.